2005
DOI: 10.1111/j.1464-5491.2005.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistin polymorphisms are associated with cerebrovascular disease in Finnish Type 2 diabetic patients

Abstract: The results suggest that resistin may play a role in atherogenesis probably through increasing insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…Possible relationships between resistin gene polymorphisms and T2DM have been investigated in various studies [20][21][22][23][24][25][26][27]. Specifically, the analysis of a Japanese population consisting of 99 T2DM patients and 99 controls did not find any associations between three intronic SNPs and T2DM [23].…”
Section: Discussionmentioning
confidence: 99%
“…Possible relationships between resistin gene polymorphisms and T2DM have been investigated in various studies [20][21][22][23][24][25][26][27]. Specifically, the analysis of a Japanese population consisting of 99 T2DM patients and 99 controls did not find any associations between three intronic SNPs and T2DM [23].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this theory, adults with MetS tend to have higher resistin levels than their healthy counterparts. 29 However, the correlation between insulin resistance and plasma resistin in adult humans remains controversial, supported by some studies 25,[35][36][37] and not in others, 4,21,34,38,39 and this therefore weakens the relation between resistin and MetS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although many studies report a lack of association between resistin gene variants and type 2 diabetes [4][5][6]10,[20][21][22][23][24][25], only one of these analyzed a sample population larger than 1000 subjects [4]. When data from three of the negative result studies [20][21][22] were analyzed together with new samples in a meta-analysis of 3536 subjects, the combined results showed an association between the −420C>G variant (RETN5) and diabetes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some genetic association analyses suggest a link between resistin gene variants and insulin resistance [4][5][6][7], while others report no such association [8,9]. Studies have found an association between certain resistin gene variants and increases in blood pressure in subjects with Type 2 diabetes mellitus, but not in controls without diabetes [4], while another reported an association between a resistin variant and hypertension only in non-diabetic controls, but not in subjects with diabetes [10].…”
Section: Introductionmentioning
confidence: 99%